Managing Granulomatous–Lymphocytic Interstitial Lung Disease in Common Variable Immunodeficiency Disorders: e-GLILDnet International Clinicians Survey - van de Ven, Annick A. J. M.; Alfaro, Tiago M.; Robinson, Alexandra; Baumann, Ulrich; Bergeron, Anne; Burns, Siobhan O.; Condliffe, Alison M.; Fevang, Børre; Gennery, Andrew R.; Haerynck, Filomeen; Jacob, Joseph; Jolles, Stephen; et al. (Frontiers in Immunology, 2020)
Background: Granulomatous–lymphocytic interstitial lung disease (GLILD) is a rare, potentially severe pulmonary complication of common variable immunodeficiency disorders (CVID). Informative clinical trials and consensus on management are lacking. Aims: The European GLILD network (e-GLILDnet) aims to describe how GLILD is currently managed in clinical practice and to determine the main uncertainties and unmet needs regarding diagnosis, treatment and follow-up. Methods: The e-GLILDnet collaborators developed and conducted an online survey facilitated by the European Society for Immunodeficiencies (ESID) and the European Respiratory Society (ERS) between February–April 2020. Results were analyzed using SPSS. Results: One hundred and sixty-one responses from adult and pediatric pulmonologists and immunologists from 47 countries were analyzed. Respondents treated a median of 27 (interquartile range, IQR 82 – maximum 500) CVID patients, of which a median of 5 (IQR 8 – max 200) had GLILD. Most respondents experienced difficulties in establishing the diagnosis of GLILD and only 31 (19%) had access to a standardized protocol. There was little uniformity in diagnostic or therapeutic interventions. Fewer than 40% of respondents saw a definite need for biopsy in all cases or performed bronchoalveolar lavage for diagnostics. Sixty-six percent used glucocorticosteroids for remission-induction and 47% for maintenance therapy; azathioprine, rituximab and mycophenolate mofetil were the most frequently prescribed steroid-sparing agents. Pulmonary function tests were the preferred modality for monitoring patients during follow-up. Conclusions: These data demonstrate an urgent need for clinical studies to provide more evidence for an international consensus regarding management of GLILD. These studies will need to address optimal procedures for definite diagnosis and a better understanding of the pathogenesis of GLILD in order to provide individualized treatment options. Non-availability of well-established standardized protocols risks endangering patients.